Structural, Physiological and Regulatory Analysis of Maltose Transporter Genes in Saccharomyces eubayanus CBS 12357T - Brickwedde, Anja; Brouwers, Nick; van den Broek, Marcel; Gallego Murillo, Joan S.; Fraiture, Julie L.; Pronk, Jack T.; Daran, Jean-Marc G. (Frontiers in Microbiology, 2018)
Saccharomyces pastorianus lager brewing yeasts are domesticated hybrids of Saccharomyces cerevisiae and cold-tolerant Saccharomyces eubayanus. To understand the contribution of both parental genomes to maltose metabolism in brewing wort, this study focuses on maltose transport in the S. eubayanus type strain CBS 12357T/FM1318T. To obtain complete sequences of the MAL loci of this strain, a near-complete genome assembly was generated using the Oxford Nanopore Technology MinION sequencing platform. Except for CHRXII, all sixteen chromosomes were assembled as single contigs. Four loci harboring putative maltose transporter genes (SeMALT1-4), located in subtelomeric regions of CHRII, CHRV, CHRXIII and CHRXVI, were completely resolved. The near-identical loci on CHRV and CHRXVI strongly resembled canonical S. cerevisiae MAL loci, while those on CHRII and CHRXIII showed different structures suggestive of gene loss. Overexpression of SeMALT1-4 in a maltose-transport-deficient S. cerevisiae strain restored growth on maltose, but not on maltotriose, indicating maltose-specific transport functionality of all four transporters. Simultaneous CRISPR-Cas9-assisted deletion of only SeMALT2 and SeMALT4, which shared 99.7 % sequence identity, eliminated growth of S. eubayanus CBS 12357T on maltose. Transcriptome analysis of S. eubayanus CBS 12357T established that SeMALT1 and SeMALT3, are poorly expressed in maltose-grown cultures, while SeMALT2 and SeMALT4 were expressed at much higher levels than SeMALT1 and SeMALT3, indicating that only SeMALT2/4 are responsible for maltose consumption in CBS 12357T. These results represent a first genomic and physiological characterization of maltose transport in S. eubayanus CBS 12357T and provides a valuable resource for further industrial exploitation of this yeast.